Diabetes and heart disease - Orchard, Trevor J. (Henry Stewart Talks, 2013)
Epidemiology, Definition and the magnitude of association in Type 1 and Type 2 diabetes, Pathology and pathogenesis, Major risk factors for heart disease in type 1 diabetes, including renal disease, insulin resistance and glycemic control, Major risk factors for heart disease in type 2 diabetes, including insulin resistance and glycemic control, Haptoglobin genotype and heart disease risk in diabetes